Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve for the roots of the function [tex]\( f(x) = (x-6)^2(x+2)^2 \)[/tex], we need to set the function equal to zero and find the values of [tex]\( x \)[/tex] that satisfy this equation. The function is zero when any of its factors are zero.
First, let's identify the factors and set them equal to zero:
[tex]\[ f(x) = (x-6)^2(x+2)^2 = 0 \][/tex]
The function will be zero if either of these factors is zero:
1. [tex]\((x-6)^2 = 0\)[/tex]
2. [tex]\((x+2)^2 = 0\)[/tex]
Solving these equations individually:
1. [tex]\((x-6)^2 = 0\)[/tex]
Solving [tex]\((x-6)^2 = 0\)[/tex], we take the square root of both sides:
[tex]\[ x - 6 = 0 \][/tex]
Therefore,
[tex]\[ x = 6 \][/tex]
The factor [tex]\((x-6)^2\)[/tex] indicates that the root [tex]\( x = 6 \)[/tex] has multiplicity 2 because the exponent of the factor is 2.
2. [tex]\((x+2)^2 = 0\)[/tex]
Solving [tex]\((x+2)^2 = 0\)[/tex], we take the square root of both sides:
[tex]\[ x + 2 = 0 \][/tex]
Therefore,
[tex]\[ x = -2 \][/tex]
Similarly, the factor [tex]\((x+2)^2\)[/tex] indicates that the root [tex]\( x = -2 \)[/tex] has multiplicity 2 because the exponent of the factor is 2.
Thus, the roots of the function [tex]\( f(x) = (x-6)^2(x+2)^2 \)[/tex] are:
- The root [tex]\( x = 6 \)[/tex] with multiplicity 2.
- The root [tex]\( x = -2 \)[/tex] with multiplicity 2.
Hence, the correct answers are:
- [tex]\( 6 \)[/tex] with multiplicity 2
- [tex]\(-2 \)[/tex] with multiplicity 2
First, let's identify the factors and set them equal to zero:
[tex]\[ f(x) = (x-6)^2(x+2)^2 = 0 \][/tex]
The function will be zero if either of these factors is zero:
1. [tex]\((x-6)^2 = 0\)[/tex]
2. [tex]\((x+2)^2 = 0\)[/tex]
Solving these equations individually:
1. [tex]\((x-6)^2 = 0\)[/tex]
Solving [tex]\((x-6)^2 = 0\)[/tex], we take the square root of both sides:
[tex]\[ x - 6 = 0 \][/tex]
Therefore,
[tex]\[ x = 6 \][/tex]
The factor [tex]\((x-6)^2\)[/tex] indicates that the root [tex]\( x = 6 \)[/tex] has multiplicity 2 because the exponent of the factor is 2.
2. [tex]\((x+2)^2 = 0\)[/tex]
Solving [tex]\((x+2)^2 = 0\)[/tex], we take the square root of both sides:
[tex]\[ x + 2 = 0 \][/tex]
Therefore,
[tex]\[ x = -2 \][/tex]
Similarly, the factor [tex]\((x+2)^2\)[/tex] indicates that the root [tex]\( x = -2 \)[/tex] has multiplicity 2 because the exponent of the factor is 2.
Thus, the roots of the function [tex]\( f(x) = (x-6)^2(x+2)^2 \)[/tex] are:
- The root [tex]\( x = 6 \)[/tex] with multiplicity 2.
- The root [tex]\( x = -2 \)[/tex] with multiplicity 2.
Hence, the correct answers are:
- [tex]\( 6 \)[/tex] with multiplicity 2
- [tex]\(-2 \)[/tex] with multiplicity 2
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.